The politics of 2011 riots in North London: How riots did not culminate into inter-ethnic conflict? - Karan, Olgu (Border Crossing, 2018)
While there has been a considerable research study into the causes and consequences of the 2011 riots and rioters’ composition in terms of their class, ethnic origin and gender, there is much less on the shop-keepers perspectives on the August, 2011 riots in London. One of the consequence of this under-research area is little is known about how riots affect relationships between communities in multi-ethnic London. Based on forty interviews conducted with Kurdish and Turkish (KT) shop-owners and key persons from community organizations in North London, the findings of this study state that the theory of middleman minorities does not provide conceptual insight to explain the events. Rather, utilization of theory of framing sheds light upon the perceptions and actions of migrants from Turkey and inter-ethnic relationships in North London. This article argues that KT shopkeepers, community organizations and rioters managed to generate a shared consciousness during face-to-face encounters on the streets. The conscious efforts of shopkeepers and rioters constructed an interest alignment against government policy for cutting social programmes, economic deprivation, and police misconduct. To this end, members of ethnic groups prevented inter-ethnic conflict.